2000
DOI: 10.1901/jaba.2000.33-239
|View full text |Cite
|
Sign up to set email alerts
|

Using Positive Peer Reporting to Improve the Social Interactions and Acceptance of Socially Isolated Adolescents in Residential Care: A Systematic Replication

Abstract: We studied how rewarding youth in residential care for publicly reporting positive social behavior influenced the social interactions and acceptance of their most socially isolated peers. Results showed that the intervention resulted in substantial improvements in social interactions by the previously isolated peers. Peer acceptance ratings also improved for 2 of the target youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…PPR involves students being rewarded for reporting on peers' positive behaviour, and has been shown to be effective in increasing positive peer interaction, and in increasing peer acceptance of children with SEBD (Ervin et al 1996;Jones, Gottfredson, and Gottfredson 1997;Bowers et al 2000;Moroz and Jones 2002).…”
Section: Teacher Utilisation Of Student Peer Influence In Classroomsmentioning
confidence: 99%
“…PPR involves students being rewarded for reporting on peers' positive behaviour, and has been shown to be effective in increasing positive peer interaction, and in increasing peer acceptance of children with SEBD (Ervin et al 1996;Jones, Gottfredson, and Gottfredson 1997;Bowers et al 2000;Moroz and Jones 2002).…”
Section: Teacher Utilisation Of Student Peer Influence In Classroomsmentioning
confidence: 99%
“…PPR is a relatively simple procedure that has been used in residential and educational settings to enhance peer interactions and peers' perceptions of students who are socially rejected or neglected (Bowers, McGinnis, Ervin, & Friman, 1999;Bowers, Woods, Carlyon, & Friman, 2000;Ervin, Johnston, & Friman, 1998;Ervin, Miller, & Friman, 1996;Jones, Young, & Friman, 2000;Robinson, 1998). Table 1 provides a basic outline of the procedure.…”
Section: Positive Peer Reporting (Ppr)mentioning
confidence: 99%
“…Subsequent studies conducted at Boys Town investigated the effects of similar interventions (Bowers et al, 1999;Bowers et al, 2000;Robinson, 1998). Across these three investigations, there were nine target students.…”
Section: Introduce and Define Positive Peer Reporting (Ppr)mentioning
confidence: 99%
“…Although the present study focused on the predictive role of emotional dysregulation over peer attachment, previous studies have suggested that peer relationships may act as an important mediator and moderator of the influence of emotional dysregulation over aggressive behaviour (Röll, Koglin, & Petermann, 2012 with peers have demonstrated interesting results, with established improvements in the quality of peer relationships and the adolescents' self-concept (Bowers, Woods, Carlyon, & Friman, 2000;James, 2011). Together, these studies and our results draw attention to the fact that both emotional dysregulation and peer attachment are interconnected, and therefore capable of influencing one another.…”
Section: Discussionmentioning
confidence: 86%